Activation of Literal Word Meanings in Idioms: Evidence from Eye-tracking and ERP Experiments. (September 2021) - Kessler, Ruth; Weber, Andrea; Friedrich, Claudia K.
How the language processing system handles formulaic language such as idioms is a matter of debate. We investigated the activation of constituent meanings by means of predictive processing in an eye-tracking experiment and in two ERP experiments (auditory and visual). In the eye-tracking experiment, German-speaking participants listened to idioms in which the final word was excised ( Hannes let the cat out of the . . . ). Well before the offset of these idiom fragments, participants fixated on the correct idiom completion ( bag ) more often than on unrelated distractors ( stomach ). Moreover, there was an early fixation bias towards semantic associates ( basket ) of the correct completion, which ended shortly after the offset of the fragment. In the ERP experiments, sentences (spoken or written) either contained complete idioms, or the final word of the idiom was replaced with a semantic associate or with an unrelated word. Across both modalities, ERPs reflected facilitated processing of correct completions across several regions of interest (ROIs) and time windows. Facilitation of semantic associates was only reliably evident in early components for auditory idiom processing. The ERP findings for spoken idioms compliment the eye-tracking data by pointing to early decompositional processing of idioms. It seems that in spoken idiom processing, holistic representations do not solely determine lexical processing.